Density functional theory investigation of CuO/ZnO/CuO heterostructure nanotubes for CO sensing applications - Mahdi Molaei Zarasvand; Mohsen Bagheritabar; Melika Molaei Zarasvand; Milad Yousefizad; Amir Mohammad Shahriyari; Erfan Karimmirza; Zahra Zalnezhad; Negin Manavizadeh; Ebrahim Nadimi (Sensing and Bio-Sensing Research)
This paper proposes a new CuO/ZnO/CuO hetero-nanotube structure for carbon monoxide (CO) sensing to improve selectivity and sensitivity. First-principles simulations based on Density Functional Theory (DFT) are employed to investigate the interaction between CO molecules and the sensor's heterostructure surface, focusing on the physicochemical properties of ZnO and CuO nanotubes. Results demonstrate that CuO/ZnO/CuO hetero-nanotube outperforms pure ZnO nanotubes. Strong chemical interactions between CO molecules and the ZnO surface within the CuO/ZnO/CuO hetero-nanotube are observed, leading to a higher adsorption energy of −2.775 eV compared to −0.018 eV for pure ZnO. This enhancement in adsorption energy and charge transfer is attributed to the potential difference between CuO and ZnO, which induces depletion layers on both sides of ZnO, altering charge distribution and enhancing gas sensitivity. The matching relaxed lattice structure drives the synergistic effect at the CuO-ZnO interface, resulting in a more responsive and stable system. Electronic transport properties significantly improve charge transfer and current-voltage characteristics under CO exposure. The sensor achieves 287.43 % sensitivity at 0.25 V, highlighting its exceptional performance. These materials offer a promising solution for developing selective, sensitive, and reliable sensors suitable for hazardous environments and automotive inspections.